Pengaruh Bentuk Tes Terhadap Hasil Belajar Matematika dengan Mengontrol Kecemasan - I Made Surat; I Putu Darmayoga (FPMIPA IKIP PGRI Bali, 2018)
The purpose of this research is as follows: 1) To find out whether there are differences of mathematics learning outcomes between students who are given a form of description test with students who are given multiple choice form tests on students of class X MIA SMA PGRI 6 Denpasar, 2) To know after held the control of anxiety variables, whether there are differences in mathematics learning outcomes between learners who are given a test form description with learners who are given multiple choice form tests on students X class MIPA SMA PGRI 6 Denpasar. This research type Quasi Experiment with design Non-Equivalent Control Group Design. The samples in this study were Class X MIA 1 and X MIA 2 consisting of 38 students each. Based on the test results hypothesis I with the help of t-test was obtained for 4,073 with a significance level of 5% was obtained for 1,993, then there are differences in learning outcomes between mathematics between students who are given the test form describing the learning outcomes of mathematics learners are given the test multiple choice form on students class X MIA SMA PGRI 6 Denpasar academic year 2017/2018. To test the hypothesis II results with one lane Anacova test obtained at 24,21, with a significance level of 5% was obtained 3,97, then after held control over the anxiety of learners, differences remain between the mathematics learning outcomes learners are given the test in narrative form with mathematics learning outcomes of learners who were given multiple choice form tests on students of class X MIA SMA PGRI 6 Denpasar academic year 2017/2018.